Tetroazolemycins A and B, Two New Oxazole-Thiazole Siderophores from Deep-Sea Streptomyces olivaceus FXJ8.012 - Liu, Ning (MDPI, 2013)
Two new oxazole/thiazole derivatives, named tetroazolemycins A (1) and B (2), have been isolated from the acetone extract of the mycelium of Streptomyces olivaceus FXJ8.012 derived from deep-sea water, together with three known compounds, spoxazomicins A–C (3–5), isolated from the fermentation supernatant. The planar structure and relative configuration of tetroazolemycins were elucidated by a combination of spectroscopic analyses, including 1D- and 2D-NMR techniques, and showed to be new pyochelin-type antibiotics. Both compounds showed metal ion-binding activity and their Zn(2+) complexes exhibited weak activity against pathogenic bacteria Klebsiella pneumoniae.